Por trás dos muros da universidade : representações de estudantes sobre o sistema de reserva de vagas (cotas) e sobre os estudantes cotistas da UFES - Guasti, Maria Cristina Figueiredo Aguiar (2014)
Analyzes the representations of students of the Universidade Federal do Espírito Santo (Ufes) on the system of vacant reserve (quotas) and on quota students. Develops the analysis from the following specific objectives: to identify the factors that contribute to the formation and reformulation of social representations with regard to being a university student; check if there are discrepancies in the representations of each group in relation to the items discussed; characterize the components that constitute the sense of belonging to the university students group and understand how to develop intra and inter groups between quota students and non-unitholders at Ufes. It is used as a methodology one single case study with multiple units of analysis, since it involved students from different courses and learning centers. Collects the data through in-depth interview to be devoted to this type of research. The number of interviewees was based on the criterion of saturation. The systematization of the data was from the content analysis of the interviews using the Theory of Social Representations. The categories were created from two aspects, the research objectives and the speeches of the students. Notes that the reception of quota students as well as the system of vacant reserve, initially drew by comparing between the conditions of competition in the entrance exam among students from public and private schools; that the sense of belonging to the group college students is realized more in relation to the university's own doings that in relation to any other condition experienced by students, including whether or not unitholder. Points for new themes to be discussed and ways to clarify students attending public secondary schools about their rights in relation to compliance with Law nº 12,711, 2012 that established the reservation of places in public higher education institutions in Brazil